Reframing Islam in Bollywood cinema: a study on the construction of the Islamic identity in Indian cinema - Raj, Sony Jalarajan; Suresh, Adith K. (My University, 2023)
This paper examines how stereotypical perceptions contribute to the construction of Muslim identity narratives in the context of Indian nationalism and the history of the Indo-Pak Partition. The main focus of this study is on how mainstream cinema portrayed the historical and nationalistic struggles of Partition through which the Muslim identity was shaped and shared through a range of communicative mediums. The verbal, physical, ritualistic and virtual modes of communication play significant roles in the construction and performance of identity. Analyzing films of mainstream Indian cinema, this article explores how expressions of the Indian Muslim are associated with the concept of Indian nationalism and its violent history of Partition and border politics where the stereotypical perceptions of Islam and Muslim identity contribute to the shaping of public opinion. It argues that whenever the corporeality of Indian Muslims is expressed through such forms, they get incorporated into the existing historic-geographical narratives, fictionalized as ideal stereotypes, normalized to fit into a particular political or ideological view, and finally get solidified into a set of polarized collective identities.
Keywords: Muslims; India; partition; nationalism; Islam; Hinduism